Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters - Aneesh, Panakkool Thamban; Helna, Ameri Kottarathil; Kumar, Appukuttan Biju; Maran, Balu Alagar Venmathi (Zootaxa, 2018)
The parasitic copepod Lernaeenicus stromatei Gnanamuthu, 1953 infecting black pomfret, Parastromateus niger (Bloch) (Carangidae) is redescribed based on a neotype and additional fresh material obtained from hosts collected at different fish landing centers on the Chennai Coast (Tamil Nadu), Malabar Coast (Kerala), and from West Bengal, India. A female L. stromatei obtained from the Chennai Coast has been designated as a neotype and deposited in the National Zoological Collections of Zoological Survey of India (NZC-ZSI). Lernaeenicus stromatei can be identified based on the following features: A long and slender body; head anteriorly rounded, dorso-ventrally flattened and slightly longer than broad; presence of three posterior horns on the head, one median and two lateral, all sub-similar and apically rounded; and an anterior neck with an indistinct partition on the dorsal side, indicating thoracic segments, and a three-jointed antennule.